2011
DOI: 10.1017/s0950268811002020
|View full text |Cite
|
Sign up to set email alerts
|

The burden of self-reported acute gastrointestinal illness in Italy: a retrospective survey, 2008–2009

Abstract: SUMMARYA retrospective telephone survey (n=3490) was conducted in Italy between 2008 and 2009 to estimate the occurrence of self-reported acute gastrointestinal illness (AGI) and to describe subjects' recourse to healthcare, using a symptom-based case definition. Three hundred and ten AGI cases were identified. The annual incidence rate was 1·08 episodes/person-year (95% confidence interval 0·90–1·14). The proportion of subjects consulting physicians was 39·5% while only 0·3% submitted a specimen for laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
63
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 19 publications
(41 reference statements)
17
63
5
1
Order By: Relevance
“…A similar seasonal AGI pattern was discovered by a study in Northern Germany who also found viral pathogens more frequently detected [22]. In neighbouring countries seasonality is similar [6,15,18] while other studies report seasonal peaks in summer [10]. There is no difference in the distribution of AGI between East and West Germany which has important implications for the interpretation of surveillance data of enteric diseases in Germany.…”
Section: Seasonality and Geographysupporting
confidence: 80%
See 1 more Smart Citation
“…A similar seasonal AGI pattern was discovered by a study in Northern Germany who also found viral pathogens more frequently detected [22]. In neighbouring countries seasonality is similar [6,15,18] while other studies report seasonal peaks in summer [10]. There is no difference in the distribution of AGI between East and West Germany which has important implications for the interpretation of surveillance data of enteric diseases in Germany.…”
Section: Seasonality and Geographysupporting
confidence: 80%
“…The methodology for community surveys has improved over the years and a common case definition was established to ensure international comparability [1][2][3]. These efforts resulted in cross-sectional studies for estimates for the burden of AGI from various countries [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and additionally a few population-based cohort studies [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The differences between parameter estimates as based on cross-sectional surveys in participating countries and literature data [5,[19][20][21][22] confirm this hypothesis. However, case numbers with bloody diarrhoea in the telephone surveys were quite small, leading to considerable uncertainty in our results.…”
Section: Limitations Of This Studysupporting
confidence: 54%
“…However, this form of listeriosis might be underestimated. A recent survey on people with self-reported acute gastrointestinal illness reported that only 36,5% sought medical assistance, and merely 2.3% of these were asked to submit a stool specimen for diagnostic investigation (Scavia et al, 2012).…”
Section: Epidemiology Of Listeriosis In Humansmentioning
confidence: 99%